On the JAP Method for the Indirect Determination of Delocalized Currents from Experimental Chemical Shifts. Issue 20 (28th July 2022) - Landi, Alessandro; Summa, Francesco F.; Zanasi, Riccardo; Monaco, Guglielmo
Abstract: The JAP model (after Jirásek, Anderson, and Peeks) to retrieve global current strengths from experimental 1 H chemical shifts has been tested with DFT computations. Both global and local tropicities are correctly predicted in most cases and the quantitative agreement is overall fair. An extension of the model is found to give improvement in an exemplary critical case, where the global delocalized current is negligible and the current density map is dominated by local currents. Abstract : Current density pathways can nowadays be reliably computed by quantum‐mechanics. But can they be obtained by experiment? The method proposed by Jirásek, Anderson and Peeks (JAP) promises to do this magic. A DFT test shows that, indeed, the method is overall successful, although it can fail in case of strongly localized currents.